Two new species of Centruroides Marx 1890 (Scorpiones: Buthidae) from Oaxaca, Mexico - Santibáñez-López, Carlos E.; Contreras-Félix, Gerardo A. (Zootaxa, 2013)
Centruroides franckei, n. sp. and Centruroides rodolfoi, n. sp. are described from Oaxaca, Mexico. These species belong to the “striped” group within the genus. Thirteen species of the genus are reported for the state, six of them belonging to the “striped” group (infamatus-nigrovariatus subgroup). Both new species are compared to their most morphological similar species. A map with the six “striped” (infamatus-nigrovariatus subgroup) species in the state is also provided.